Importance of the coronary circulation for cardiac and metabolic performance in rainbow trout (Oncorhynchus mykiss). (31st July 2018) - Ekström, Andreas; Axelsson, Michael; Gräns, Albin; Brijs, Jeroen; Sandblom, Erik
Abstract : Cardiac oxygenation is achieved via both coronary arterial and luminal venous oxygen supply routes in many fish species. However, the relative importance of these supplies for cardiac and aerobic metabolic performance is not fully understood. Here, we investigated how coronary artery ligation in rainbow trout ( Oncorhynchus mykiss ), implanted with heart rate loggers, affected cardiorespiratory performance in vivo . While coronary ligation significantly elevated resting heart rate, the standard metabolic rate was unchanged compared to sham-treated controls. However, coronary ligation reduced the maximum metabolic rate while heart rate remained unchanged following enforced exercise. Thus, coronary ligation reduced metabolic and heart rate scopes by 29% and 74%, respectively. Our findings highlight the importance of coronary oxygen supply for overall cardiorespiratory performance in salmonid fish, and suggest that pathological conditions that impair coronary flow (e.g. coronary arteriosclerosis) constrain the ability of fish to cope with metabolically demanding challenges such as spawning migrations and environmental warming.